PENGARUH FAKTOR-FAKTOR EKSTERNAL BURNOUT AKADEMIK ATAU INTENSITAS MEDIA SOSIAL - Yusran, Iki; Selviani, Selviani; Kahar, Sirma (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Academic burnout has emerged as a critical psychological issue among university students in the digital era, particularly as academic demands intensify alongside the increasing use of social media. This study aims to examine the influence of external factors and the intensity of social media use on students’ academic burnout. Employing a quantitative explanatory survey design, the research involved 214 university students selected through purposive sampling. Data were collected using a structured questionnaire that measured family pressure, peer influence, environmental disturbances, social media intensity, digital-induced anxiety, sleep disruption, and indicators of academic exhaustion. Descriptive statistical analysis revealed that external factors significantly contributed to burnout, with 72.4% of students reporting family pressure, 60.7% influenced by peer dynamics, and 44.9% experiencing physical environmental disturbances. Moreover, high social media intensity exacerbated burnout, as indicated by disrupted study time (59.8%), academic procrastination (54.7%), digital anxiety (60.7%), and reduced sleep quality (55.6%). The findings indicate a strong interactive effect between external stressors and maladaptive digital behavior in intensifying academic burnout. This study concludes that academic burnout is shaped by the cumulative impact of environmental pressures and excessive social media use, highlighting the need for comprehensive interventions such as strengthened social support, digital literacy programs, and healthier media engagement strategies to mitigate burnout risk among university students.